2008
DOI: 10.1002/anie.200803446
|View full text |Cite
|
Sign up to set email alerts
|

Strong, Localized, and Directional Hydrogen Bonds Fluidize Ionic Liquids

Abstract: Hydrogen bonds are very important in chemistry and biology. [1][2][3] The properties of liquids and solutions consisting purely of neutral molecules are characteristically determined by the strength and number of hydrogen bonds. When water freezes to form ice, each water molecule forms four strong hydrogen bonds to its neighbors in tetrahedral fashion giving a periodical H-bond network.[4] In nonpolar solvents peptides retain their helical secondary structure up to very high temperature as a result of intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
456
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 413 publications
(498 citation statements)
references
References 27 publications
(46 reference statements)
28
456
1
8
Order By: Relevance
“…In the real liquid, a distribution of several cation/anion configurations will be present simultaneously [43], and the sketch must be seen as one example of what the data suggest exists in larger amounts. in computational studies [4,5,7,28,29,38]. This suggests that the above findings represent a rather universal phenomenon.…”
Section: Nmr Spectramentioning
confidence: 66%
See 2 more Smart Citations
“…In the real liquid, a distribution of several cation/anion configurations will be present simultaneously [43], and the sketch must be seen as one example of what the data suggest exists in larger amounts. in computational studies [4,5,7,28,29,38]. This suggests that the above findings represent a rather universal phenomenon.…”
Section: Nmr Spectramentioning
confidence: 66%
“…The list of investigated anions includes bis(trifluoromethylsulfonyl) imide [4][5][6][7], nitrate [8], alkyl sulfates [5,9], dicyanamide [5,10], thiocyanate [5], acetate [11,12], hydrogen sulfate [13,14], and trifluoromethanesulfate [15,16]. On the other hand, interactions with highly symmetrical anions have been studied less.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imidazolium-based ILs are reported to form ionic hydrogen bonds of the form C(2)-H y A À (A, anion), and bonds formed between 1-ethyl-3-methyl-imidazolium and TFSA anion were reported by Fumino et al 36 Meanwhile, ILs with TFSA anions were reported to possess a significantly smaller cohesive energy density than water. 13 The observation that 1 and 2 are molecularly dispersed in C 4 mimTFSA without forming self-assemblies can be understood by the insufficient difference in cohesive energy between 1, 2 and C 4 mimTFSA.…”
Section: Resultsmentioning
confidence: 98%
“…It should also be noted that ILs can be amphiphilic 35 and capable of forming ionic hydrogen bonds. 36 We describe herein the formation of bilayer membranes in ILs for a series of aqueous-bilayer-forming cationic glutamate amphiphiles. The intermolecular interactions required for self-assembly in ILs vary depending on the chemical structure of ILs, and these results provide a general guideline to design ordered molecular self-assembly systems in ILs.…”
Section: Introductionmentioning
confidence: 99%